Trichinella patagoniensis n. sp. (Nematoda), a new encapsulated species infecting carnivorous mammals in South America - Krivokapich, Silvio (2012)
Fil: Krivokapich, Silvio. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Parasitología; Argentina.